Relationship between Tobacco Use and Health-Related Quality of Life (HRQoL) among Clients in Substance Use Disorders Treatment. Issue 1 (1st January 2019) - Campbell, Barbara; Yip, Deborah; Le, Thao; Gubner, Noah; Guydish, Joseph
ABSTRACT: We examined relationships of smoking status and tobacco-related variables with health-related quality of life (HRQoL), a metric of disease burden, among clients in substance use disorders (SUDs) treatment. Participants ( N = 2, 068; 46.6% female) completed surveys reporting demographics, smoking status, and past-month days they experienced physical and/or mental health distress. Smokers ( n = 1, 596; 77.2% of sample) answered questions on tobacco-related variables. Multinomial regression models assessed relationships between tobacco-related variables (smoking status, nicotine dependence, menthol smoking, electronic-cigarette use, health concerns, and cost as reasons affecting reducing/quitting smoking, past and future quit attempts) with HRQol in four categories (good health, physical health distress, mental health distress, or both physical and mental health distress). Current smokers were more likely than former smokers to report frequent physical and mental health distress than good health (OR = 1.97, 95% CI = 1.16, 3.34), as were smokers with higher nicotine dependence (OR = 1.18, 95% CI = 1.03, 1.35). Smokers reporting both frequent physical and mental health distress were more sensitive to cigarettes' cost (OR = 1.56, 95% CI = 1.06, 2.29), and less likely to use e-cigarettes (OR = 0.59, 95% CI = 0.38, 0.94). Findings of poor HRQoL among nicotine-dependent smokers with additional SUDs strengthen the imperative to provide smoking cessation interventions in addictions treatment.